Emerging technologies for food processing - Sun, Da-Wen (Food science and technology international series., 2005)
Emerging Technologies for Food Processing presents a comprehensive review of innovations in food processing, stresses topics vital to the food industry today, and pinpoints the trends in future research and development. This volume contains 27 chapters and is divided into six parts covering topics such as the latest advances in non-thermal processing, alternative technologies and strategies for thermal processing, the latest developments in food refrigeration, and current topics in minimal processing of vegetables, fruits, juices and cook-chill ready meals and modified atmosphere packaging for minimally processed foods. * Each chapter is written by international experts presenting thorough research results and critical reviews * Includes a comprehensive list of recently published literature * Covers topics such as high pressure, pulsed electric fields, recent developments in microwave heating, and vacuum cooling.